Validitas Jobsheet Mata Kuliah Praktek Pengaman Peralatan dan Pembumian Departemen Teknik Elektro - Rahmat Reymonri; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2023)
Education is the key to improving the quality of superior human resources (HR) capable of responding to future challenges. Education aims for each individual to have the useful experience that comes from the teaching and learning process so that they have the desired human resources. Quality human resources can only be obtained from a quality education process. Jobsheet is a learning medium in the form of work procedures and guidelines for students or when doing practicum which contains materials and instructions for practicum implementation. The method used in this study was a pre-experimental research design with a One Shot Case Study design. The research aimed at developing the job sheet for the Equipment Safety and Earthing Practice course, D3 Electrical Engineering Study Program, FT UNP and knowing the level of validity of the job sheet for the Equipment Safety and Earthing Practice course, D3 Electrical Engineering Study Program, Department of Electrical Engineering, FT UNP. This research involved two lecturers as validators who are experts in their fields, namely media experts and material experts. In the media expert's assessment, the results of the testers were very good and declared valid. Whereas in the material expert assessment, the results obtained from the testers were very good and declared valid. Meanwhile, the practicality test conducted on 19 students obtained very good and stated results. So, by obtaining the results of the research conducted, it is expected that the jobsheets developed can be useful for lecturers and students for future practicum lectures.